Mach 2 rarefied airflow over a plate submitted to a DC discharge: surface temperature gradient investigation. (2015) - Parisse, Jean-Denis; Kudryavtsev, Alexey N.; Lago, Viviana
This study is devoted to a much deeper understanding of the interaction between a rarefied Mach 2 airflow surrounding a flat plate and a DC discharge. In previous works, it has been demonstrated that the interaction is mainly due to the plate surface thermal heating, whereas numerical simulations have been achieved with isothermal hypothesis. The aim of this work is to have a much precise description of this interaction by taking into account thermal gradient of the surface heating. This should lead to a much better agreement between simulations and experimental results and so improve the understanding of the physical phenomena involved.